High incidence of dioecy in young successional tropical forests. (20th March 2015) - Réjou‐Méchain, Maxime; Cheptou, Pierre‐Olivier; Fridley, Jason
Summary The role of plant sexual systems in community assembly has been little studied. Classical assumptions predict an association between self‐fertilization and colonizing ability, a pattern not systematically supported by observations. Here, using a data set of 626 462 trees sampled throughout 8300 km2 in central Africa and historical information collected 60 years ago on forest successional status, we compare sexual system assemblages between young successional and mature communities. We use two multivariate approaches to assess the variation in community dioecism between successional status, while controlling for covariation between dioecy and six other traits usually considered as good proxies for important functions in forest successional dynamics. We show that dioecious trees are significantly overrepresented in young successional areas, contrary to classical expectations. This robust pattern is unlikely to be driven by soil conditions, by the other associated traits or by species‐specific abundance. Strikingly, dioecy was one of the traits most correlated with young successional areas. These results show that sexual systems play an important role in community assembly. The higher occurrence of dioecy in young successional areas is likely due to a higher relative seed fitness of dioecious species in more stressful conditions or by an evolutionary‐driven association between dioecy and colonization ability, as predicted by theoretical studies. Synthesis. Our study emphasizes an overlooked association between sexual system and community assembly and emphasizes the need to revisit classical assumptions regarding that relationship.